Involvement of Faculty in Research and Community Extension - Mobo, Froilan Delute; Siahaan, Sanggam; Saadoon, Abather; Panigrahi, Rashmi Ranjan (LPPM Universitas PGRI Sumatera Barat, 2023)
The academic world is full of scientific surprises because education is changing so rapidly because of its alignment with various sectoral fields. One of the requirements to be called a lecturer is to be involved in three fields: teaching, research, and involvement in community outreach; and has been published in peer-reviewed reputable journals indexed in Scopus, Web of Science, ISI, and other high-impact databases. The purpose of this research was to analyze Most of the universities experienced difficulties requiring their faculty to be actively involved in research and community outreach, and several factors influenced their willingness to pursue such initiatives. The type of research method used is a qualitative research method, which will identify how to motivate lecturer involvement in research and community service. The results showed that the majority of respondents or 85.7% preferred the reward system to encourage faculty involvement in research and community outreach, while the remaining 24 respondents preferred awards, which could range from other collaborations with research with other universities and colleges in the Philippines. Figure 2 shows that the majority of respondents prefer the formation of open research working groups with a total of 50 respondents, 100%, which means strengthening research collaboration will strengthen faculty motivation to engage in research, development, and counseling.